IMPLEMENTASI PENGGUNAAN WORDWALL DALAM MENGEVALUASI PEMBELAJARAN PAI DI SMP AL-HAMIDIYAH BANGKALAN - Muhammad Ikhsan; Irma Soraya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Wordwall is a web application used to create fun test-based games. With wordwall a wide variety of game models can be created. Wordwall can be used as an approach to form new interests of students in learning. Wordwall is acceptable and enjoyable learning without losing the substance of continuous learning. Wordwall is a learning media that can be used anywhere. This media can be designed so that it can be carried out in study group activities and involve one student with another. This research method is in the form of descriptive qualitative as a scientific method used by a group of researchers in the field of education. According to Johny Saldana, research focuses on social life using materials that are visual and descriptive. While the qualitative approach according to Jhon W Creswell can also be said to be an activity to study an individual or group activity that describes a problem. Based on the results of research and discussion of the Use of Wordwall in the Evaluation of Islamic Religious Education Subjects at SMP Al-Hamidiyah Bangkalan, it was concluded that the use of wordwall in process evaluation with the maze chase feature helps teachers attract the interest and attention of students in conducting evaluation activities in the form of quizzes.